Cobitis avicennae, a new species of spined loach from the Tigris River drainage (Teleostei: Cobitidae) - Mousavi-Sabet, Hamed; Vatandoust, Saber; Esmaeili, Hamid Reza; Geiger, Matthias F.; Freyhof, Jörg (Zootaxa, 2015)
Cobitis avicennae, new species, from the Karkheh and Karun sub-drainages in the Tigris catchment is distinguished from other Cobitis species in the Persian Gulf, Kor and the southern Caspian Sea basins by having a single lamina circularis in males, a small comma-shaped black spot on the upper caudal-fin base, 5½ branched anal-fin rays, 5–6 rows of dark spots on the dorsal and caudal fins, scales below the dorsal-fin base with a small focal zone and pigmentation zone Z4 with 12–17 large, partly fused blotches. It is also distinguished from other Cobitis species in the comparison group by six fixed, diagnostic nucleotide substitutions in the mtDNA COI barcode region.